2017
DOI: 10.5489/cuaj.4927
|View full text |Cite
|
Sign up to set email alerts
|

CanMEDS scholars: A national survey on urology residents’ attitudes towards research during training

Abstract: Introduction: Participation in scholarly activity is an important tenet of residency training and is firmly entrenched in Canada since the introduction of CANMEDS roles by the Royal College of Physicians and Surgeons. As Canadian residency programs transition to competency-based training, it will remain important to understand how to best implement and encourage scholarly pursuits among resident trainees. The objective of this study was to understand the experiences, attitudes, and barriers that surgical resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Mentorship is an influential factor in a thriving research experience. 10,20,24,25 Prior studies have reported a lack of proper mentoring as a significant barrier for research. 4,8 Residents of TUOMS were less motivated to do research due to 1) mandatory research topics and 2) advisors/ mentors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentorship is an influential factor in a thriving research experience. 10,20,24,25 Prior studies have reported a lack of proper mentoring as a significant barrier for research. 4,8 Residents of TUOMS were less motivated to do research due to 1) mandatory research topics and 2) advisors/ mentors.…”
Section: Discussionmentioning
confidence: 99%
“…Time for research is crucial in clinical residency. 4,8,10,25,26 In the TUOMS research program, a protected one month period during the first year of residency was allocated to proposal writing, but program directors did not consider a similar protected time for research execution. Although one month of protected time helped residents complete proposals, it caused understaffed wards, scheduling difficulties, and residents missing some clinical experience.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 24 articles employed quantitative methods, 1,3,4,7,10,34,36,37,39,40,42,88-100 3 were qualitative, 101-103 5 used mixed methods, 9,38,45,104,105 8 were literature reviews, 2,8,11,18,31,35,106,107 5 were perspective papers, 6,30,32,33,43 3 were descriptive in nature, 41,44,108 and 2 were systematic reviews. 5,109 Nineteen studies in-volved mentees only, 3,4,32,36,40,42,45,88,90,92,94-96,98,99,…”
Section: Stage 4: Data Characterisation and Analysismentioning
confidence: 99%
“…Lack of institutional support 1,3,8,10,11,18,[34][35][36][37]39,41,[90][91][92]95,97,98,104,[107][108][109] Poor access to trained mentors 1,4,5,18,[35][36][37][38][39]90,91,95,97,102,104,107,108 Poor access to same-sex mentors 1,2,5,7,9,11,18,31,35,36,40,91,100,105,…”
Section: Role Of Host Organisationmentioning
confidence: 99%
See 1 more Smart Citation